Lobbying hitler: industrial associations between democracy and dictatorship - Bera, Matt (Berghahn Books, 2016)
From 1933 onward, Nazi Germany undertook massive and unprecedented industrial integration, submitting an entire economic sector to direct state oversight. This innovative study explores how German professionals navigated this complex landscape through the divergent careers of business managers in two of the era's most important trade organizations. While Jakob Reichert of the iron and steel industry unexpectedly resisted state control and was eventually driven to suicide, Karl Lange of the machine builders' association achieved security for himself and his industry by submitting to the Nazi regime. Both men's stories illuminate the options available to industrialists under the Third Reich, as well as the real priorities set by the industries they served.